A String of beads - Perry, Thomas, 1947- (Perry, Thomas, 1947- Jane Whitefield novel (Tantor Media), 2014)
After two decades spent protecting innocent victims on the run, and a year after getting shot on a job that took a dangerous turn for the worse, Jane McKinnon, née Whitefield, has settled into the quiet life of a suburban housewife in Amherst, New York--or so she thinks. One morning as she comes back from a long run, Jane is met by an unusual sight: the eight female leaders of her Seneca tribe parked in her driveway in two black cars. A childhood friend of Jane's from the reservation, Jimmy, is wanted by the police for the murder of a local white man. But instead of turning himself in, he's fled, and no one knows where he is hiding out. At the clan mothers' request, Jane retraces a walking trip she and Jimmy took together when they were fourteen in hopes that he has gone the same way again. But it soon becomes clear that the police aren't the only ones after him.